a. D

45. Both equations of the law of ABSORPTION, A(A+B) =A and

b. AQ

A+(AB) =A can be proved by applying the laws of Boolean Algebra

c. X

shown below.

d. EZ

A(A+B) =A

AA+AB=A

DISTRIBUTIVE

A+AB=A

IDEMPOTENT

A(1 +B) =A

DISTRIBUTIVE

A 1=A

UNION

A=A

INTERSECTION

A+(AB) =A

A+AB=A

ASSOCIATIVE

A(1 +B) =A

DISTRIBUTIVE

A 1=A

UNION

A=A

INTERSECTION

Since both equations are equal to A, it is mathematically correct

that A(A+B) =A+AB.

Simplify the following Boolean expressions, using the law of

ABSORTPION.

a. D+DE

b. K+KL+KM

c. TGNE+T+TI

d. V+W+WX